Predicting Elective Orthopaedic Sports Medicine Surgical Cancellations Based on Patient Demographics - Brandon Petrone, D.O; Jordan Fakhoury, D.O; Prashant Matai, M.B.B.S; Adam Bitterman, D.O; Randy M. Cohn, M.D; Larry Lutsky, Ph.D (Elsevier, 2020)
Purpose: To evaluate whether patient demographics are associated with cancellation of elective orthopaedic sports medicine surgical procedures. Methods: We retrospectively reviewed the electronic medical records of 761 patients who were scheduled to undergo an elective sports medicine orthopaedic operation from January 1, 2015, to December 31, 2017. The patients were divided into 2 groups: those who underwent the scheduled procedure (group A) and those in whom the operation was canceled for any reason prior to the surgical date and not rescheduled (group B). Univariate analysis assessed patient factors consisting of age, sex, race, language, marital status, occupation status, type of insurance (Medicaid or Medicare vs private), smoking history, employment status, and history of surgery to determine which demographic factors led to an increased risk of elective case cancellation. Results: Patients who canceled were significantly older (46.5 years vs 41.5 years, t = 2.432, P = .015) than those who do not. In addition, current smokers (22.5% vs 10.9%, χ2 = 10.85, P = .001), patients with Medicare or Medicaid versus private insurance (16.7% vs 10.0%, χ2 = 5.35, P = .021), non-English-speaking patients (29.5% vs 11.6%, χ2 = 11.43, P = .001), and patients without a history of surgery requiring anesthesia (18.8% vs 9.6%, χ2 = 9.96, P = .002) were all more likely to cancel. When all studied variables were examined in a logistic regression analysis, of the above demographic variables, only insurance status was no longer significant, given its correlation with age and language. Conclusions: Increased age (≥46.5 years), non-English speaking, smoking, lack of a history of surgery requiring anesthesia, and Medicaid or Medicare insurance were found to contribute to an increased risk of elective orthopaedic surgery cancellation. Level of Evidence: Level III, case-control study.